Displacement and dynamic weakening processes in smectite‐rich gouge from the Central Deforming Zone of the San Andreas Fault. Issue 3 (21st March 2014) - French, M. E.; Kitajima, H.; Chester, J. S.; Chester, F. M.; Hirose, T.
<x xml:space="preserve">Abstract</x> The strength of clay‐rich gouge from the Central Deforming Zone (CDZ) of the San Andreas Fault (SAF) was measured using a high‐speed rotary shear apparatus to evaluate the potential for unstable slip along the creeping segment of the SAF. Wet and dry gouge was sheared at 0.1–1.3 m/s, 0.5–1.5 MPa normal stress, and 1–20 m displacement. CDZ gouge is weaker wet than dry and exhibits displacement strengthening to peak friction followed by weakening to steady state strength that decreases with increasing velocity. A clay foliation (Unit 2) develops from the initial microstructure (Unit 1) during the first 1.5 m of slip coincident with increasing strength. Subsequent weakening occurs during shear within Unit 2, and subsequently with development of a localized foliated slip zone (Unit 4) and fluidized material (Unit 3). Displacement and dynamic weakening result from slip along clay foliation assisted by shear‐heating pressurization of pore fluid in wet gouge and additional grain‐size reduction and possible clay dehydration in dry gouge. Peak strength is proportional to normal stress, but steady state strength is insensitive to normal stress probably because pore pressure approaches the normal stress. As such, CDZ gouge is weak at coseismic rates relative to interseismic creep strength. The potential for sustaining rupture propagation into the CDZ from an adjacent seismic segment is sensitive to the relationship used to extrapolate the critical weakening displacement from experimental to in situ conditions. Rupture propagation from a microseismic patch within the CDZ is unlikely, but sustained propagation from a large earthquake (e.g., Parkfield event) may be possible.